ANALISIS YURIDIS PERJANJIAN JUAL BELI MELALUI MEDIA ELEKTRONIK BERDASARKAN KUH PERDATA DAN UNDANG - UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Fauzi, Anggit Rahmat; Ansari, Ansari (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2020)
The utilization of e-commerce media in the trading world brings impact to the international community in general and the people of Indonesia in particular. For Indonesian people, This is related to a very important legal problem. The importance of law in the field of e-commerce is mainly in protecting the parties who transact through the Internet. The purpose of this study is to know the legal review of the buying and selling agreements through electronic media as well as to know the legal protections for sellers and buyers if one of the parties commits a default. The research uses a normative juridical method of approach and the discussion is done in a descriptive analysis. The source and type of data used are primary data and secondary data. While the data collection techniques using literature studies, and the data obtained will be analyzed qualitatively. The agreement to buy and sell through electronic media is a new phenomenon that has been implemented in various countries and regulated in the Civil state nor law ITE. Legal protection for the parties in the sale and purchase agreements through electronic media is governed by the consumer protection ACT. Any breach must respond to any loss arising from his or her actions.